The Impact of the Multiliteration Learning Model on the Ability to Read Comprehension and Creative Writing of Fifth Grade Elementary School Students - Fudhaily, Ahmad Wahid; Rahman (Universitas Pendidikan Ganesha, 2022)
Student’s ability to read and write is important in obtaining an education. It's just that the reality on the ground shows that students' reading and writing skills are still in the low category. The purpose of this study is to determine the influence of the multiliteracy learning model used by the teacher on reading comprehension and creative writing skills. This study uses a quantitative approach with the method of exposure to facts. The population in this study was fifth-grade elementary school students, totaling 155 people. Sampling in the study was carried out by incidental sampling technique with a final sample size of 15 fifth-grade elementary school students. Data collection in the study was carried out using test and non-test techniques with research instruments such as observation sheets and tests of students' reading and writing abilities. The study results indicate that the correlation coefficient test indicates that the R-score is 0.377. The X variable affects two variables simultaneously: the X variable with Y1 and Y2. Based on these results, it can be concluded that the multiliteracy learning model has more influence on the ability to read comprehension than the creative writing ability of students. However, the effect is not so significant.